2022
DOI: 10.34172/jqr.2022.10
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Positive Couple Interactions after Myocardial Infarction: A Qualitative Study

Abstract: Background: The quality of marital relationships can impact couples’ cardiovascular health directly and indirectly. Given that communication is essential for a happy marriage and plays an important role in health, this study aimed to explain the positive interactions of couples after myocardial infarction. Methods: The current study was conducted qualitatively with the participation of seven couples (patient and his or her spouse) in teaching hospitals affiliated with Zahedan University of Medical Sciences. Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Fletcher et al (2000) confirmed the six-factor structure and reported Cronbach's alpha (α) coefficients ranging from .74 to .96. In another study, Sarhadi et al (2013) confirmed the six-factor structure and obtained a Cronbach's alpha (α) coefficient of .86. In this study, the subscales of satisfaction, commitment, intimacy, and trust were used.…”
Section: The Perceived Relationship Quality Component (Prqc; Fletcher...mentioning
confidence: 78%
“…Fletcher et al (2000) confirmed the six-factor structure and reported Cronbach's alpha (α) coefficients ranging from .74 to .96. In another study, Sarhadi et al (2013) confirmed the six-factor structure and obtained a Cronbach's alpha (α) coefficient of .86. In this study, the subscales of satisfaction, commitment, intimacy, and trust were used.…”
Section: The Perceived Relationship Quality Component (Prqc; Fletcher...mentioning
confidence: 78%